FROM SILHOUETTE TO IDENTITY: THE IMPLEMENTATION OF SHOE MODELS IN AIR JORDAN'S SEMIOTIC LITERACY ASSISTANCE FOR THE SNEAKER LOVING COMMUNITY - Ahmad Zulkifli; Akhmad Taufik (International Journal of Society and Law, 2026)
Sneaker culture has evolved from footwear use into a space for expressing identity, community affiliation, nostalgia, and symbolic consumption. Air Jordan occupies a prominent position in this culture by combining sports history, design, celebrity narratives, scarcity, and collectible value. Nevertheless, enthusiasm for models, colorways, collaborations, and resale prices is not always accompanied by the ability to read signs critically. This community service article introduces the SEPATU Model as an accessible semiotic literacy mentoring approach for sneaker communities. SEPATU stands for observing signs, exploring contexts, mapping meanings, analysing sign systems, examining authenticity, and testing consumption decisions. The program is designed through a participatory sequence consisting of an initial assessment, an introduction to semiotics, an Air Jordan object clinic, group discussion, presentation of analyses, and critical-consumer reflection. Evaluation uses pretest-posttest instruments, analysis worksheets, participation observations, and satisfaction surveys. The model connects the concepts of icon, index, symbol, denotation, connotation, and myth with product knowledge and ethical consumption considerations. Its primary outputs are a concise learning module, a sign-reading matrix, and a purchasing-decision checklist. Conceptually, the SEPATU Model expands community engagement in communication and design by moving beyond product aesthetics toward a critical understanding of the relationships among signs, identity, popular culture, authenticity, and responsible consumption decisions.